2011
DOI: 10.1007/s00265-011-1256-5
|View full text |Cite
|
Sign up to set email alerts
|

The anti-predator behaviour of wild white-handed gibbons (Hylobates lar)

Abstract: Predation on gibbons is rarely observed in the wild. However, the gibbons' moderate body size and relatively small social groups suggest high vulnerability to predation. To assess the role of predation and to study their anti-predator behaviour, we presented visual predator models to nine groups of wild white-handed gibbons at Khao Yai National Park, Thailand. We measured subjects' immediate and delayed responses to four potential predators: tiger, clouded leopard, crested serpent eagle and reticulated python.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
3
18
0
Order By: Relevance
“…Southeast Asian hawk‐eagles are considerably smaller than crowned eagles in Africa and harpy eagles of the Neotropics, which could explain why gibbons and adult colobines (for example, Rhinopithecus , Presbytis ) in Asia are at reduced predation risk . Indeed, field experiments showed that gibbons respond very strongly to clouded leopard and tiger models, but only weakly to crested serpent eagle models, suggesting that raptors may not be perceived as threats . Several large eagles have distributions that include those of gibbons; however, to date, no act of predation, by raptor or otherwise, has been witnessed at any gibbon study site …”
Section: Primates Known or Strongly Suspected Of Having Been Killed Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Southeast Asian hawk‐eagles are considerably smaller than crowned eagles in Africa and harpy eagles of the Neotropics, which could explain why gibbons and adult colobines (for example, Rhinopithecus , Presbytis ) in Asia are at reduced predation risk . Indeed, field experiments showed that gibbons respond very strongly to clouded leopard and tiger models, but only weakly to crested serpent eagle models, suggesting that raptors may not be perceived as threats . Several large eagles have distributions that include those of gibbons; however, to date, no act of predation, by raptor or otherwise, has been witnessed at any gibbon study site …”
Section: Primates Known or Strongly Suspected Of Having Been Killed Bmentioning
confidence: 99%
“…69 Indeed, field experiments showed that gibbons respond very strongly to clouded leopard and tiger models, but only weakly to crested serpent eagle models, suggesting that raptors may not be perceived as threats. 78 Several large eagles have distributions that include those of gibbons; however, to date, no act of predation, by raptor or otherwise, has been witnessed at any gibbon study site. 79 From taphonomic studies of extant prey and fossil assemblages, we have developed a good understanding of how owls and other raptors feed on and modify bones of small-bodiedand micro-mammals.…”
mentioning
confidence: 99%
“…Although one‐zero sampling has received criticism (e.g., Altmann, ), this sampling method has also been empirically shown to be an effective technique for collecting data on primate behavioural rates (Leger, ; Rhine & Linville, ; Sarfaty, Margulis, & Atsalis, ; Suen & Ary, ), and has been used in other studies on primate vocalisations (e.g., Bolt, ,c, ; Bolt et al., ; Clarke, Reichard, & Zuberbühler, ; Suzuki & Sugiura, ). We used one‐zero sampling because Bernstein () recommended that one‐zero scoring should be used when behavioural acts are clustered and the bout, rather than each act, is of interest.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Clarke et al [78] found that Lar gibbons showed long-term behavioural effects hours after exposure to a predator model. A sensible way to avoid negative consequences is to work with stimuli that already occur regularly in the animals' natural lives.…”
Section: Experimenting With Intelligent Speciesmentioning
confidence: 99%